2015
DOI: 10.1186/s12881-015-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific associations between ADIPOQ gene polymorphisms and adiponectin levels and obesity in the Jackson Heart Study cohort

Abstract: BackgroundDespite the important role of adiponectin in regulating general metabolic homeostasis, analysis of genetic determinants of adiponectin and the related cardio-metabolic traits in African American population has been limited and inconsistent.Considering the high genetic admixture of African Americans and thus the important population stratification that may confound the genetic-trait associations, the objective of this work was to perform a comprehensive analysis of the associations between ADIPOQ vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 59 publications
(77 reference statements)
1
27
0
1
Order By: Relevance
“…Several SNPs of the adiponectin gene (APIDOQ; rs6444174, rs1403697, rs7641507 and rs16861205) have been found to be associated with serum adiponectin levels in women but not men (Riestra et al 2015). Additionally, one of those SNPs (rs6444174) was found to be associated directly with BMI and obesity (Riestra et al 2015). Although a role of E2 in APIDOQ gene polymorphisms has not been elucidated, certainly there are differences in APIDOQ genetic determinants by gender and with respect to WAT mass.…”
Section: Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Several SNPs of the adiponectin gene (APIDOQ; rs6444174, rs1403697, rs7641507 and rs16861205) have been found to be associated with serum adiponectin levels in women but not men (Riestra et al 2015). Additionally, one of those SNPs (rs6444174) was found to be associated directly with BMI and obesity (Riestra et al 2015). Although a role of E2 in APIDOQ gene polymorphisms has not been elucidated, certainly there are differences in APIDOQ genetic determinants by gender and with respect to WAT mass.…”
Section: Adiponectinmentioning
confidence: 99%
“…Further studies are needed to more conclusively determine the effects of E2 on adipokine secretion. Several SNPs of the adiponectin gene (APIDOQ; rs6444174, rs1403697, rs7641507 and rs16861205) have been found to be associated with serum adiponectin levels in women but not men (Riestra et al 2015). Additionally, one of those SNPs (rs6444174) was found to be associated directly with BMI and obesity (Riestra et al 2015).…”
Section: Adiponectinmentioning
confidence: 99%
“…In recent years, there have been many reports about the association between adiponectin SNPs and various diseases. Although previous studies have examined the role of adiponectin SNPs in obesity, T2D and CVD [11][12][13][14][15]37 . In this study, we did not find a significant association between the +45 T>G (rs2241766) in the ADIPOQ gene and MS in Tunisian population.…”
Section: Discussionmentioning
confidence: 99%
“…Riestra et al [11], Davis et al [20], and Ong et al [21] certified that SNPs rs12495941, rs182052, and rs16861205 were associated significantly with adiponectin levels. However, no previous studies examining the association between rs12495941, rs182052, and rs16861205 with the risk of OSAS have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a clinical study by Al Mutairi et al [10] demonstrated that adiponectin is an independent marker of disease severity in patients with OSAS. One or more single nucleotide polymorphisms (SNPs) in the ADIPOQ gene affect the synthesis and secretion of adiponectin, indicating that genetic variation within the ADIPOQ gene may be a determinant of serum adiponectin level [11], and such alterations might contribute to increased susceptibility of OSAS. Taken together, it seems reasonable to speculate that adiponectin variants are involved in the etiology of OSAS.…”
Section: Introductionmentioning
confidence: 99%